FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA JUAL KARET DI DESA KEBUNJATI DI KECAMATAN SEMIDANG AJI KABUPATEN OKU - Agustina, Melly; Pusvita, Ema; Septianita, Septianita (Universitas Galuh, 2023)
This study has directions to find out the factors that influence the selling price of rubber in Kebunjati Village, Semidang Aji District, OKU Regency. This research method was carried out using a quantitative method in which the research used multiple linear regression analysis. Data was obtained by distributing questionnaires and data obtained from rubber farmers in Kebunjati Village. The results of this study are the factors that influence the selling price of rubber in Kebunjati Village, namely there are 3 factors including: place of sale, rubber quality and slab storage time. Of the three factors that greatly influence, namely the place of sale and the quality of rubber with a significant level of 1% and one factor that has a significant effect on the selling price of rubber in Kebunjati Village, namely the long period of storage of slabs with a significant level of 30%.